Psychosocial factors and work stress in civil servants: a scoping review - Putra, Arie Januarius; Erwandi, Dadan (BKM Public Health and Community Medicine, 2025)
Purpose: Occupational stress is a challenge in occupational health that can affect worker and company productivity. Government employees often face a high workload, but research on work stress among them is limited. Therefore, through a scoping review, this study examined the psychosocial factors influencing workload among civil servants. Methods: Following JBI Scoping Review guidelines, literature was retrieved from PubMed, ScienceDirect, ProQuest, and Google Scholar. Screening and full-text reviews were conducted using Rayyan, with descriptive synthesis applied. Studies on medical and security personnel and COVID-19-specific stress were excluded. Results: Of the 970 articles identified, 11 studies met the inclusion criteria and were analyzed in this scoping review. The most dominant psychosocial factors influencing civil servants' work stress were their relationship with the organization and work environment (45.5%), followed by job demands (36.4%) and work-family balance (36.4%). Other factors contributing to job stress included job control, career prospects, supervisor support, and job dissatisfaction, while public motivation and social support were found in 1 study. Conclusion: Civil servants’ work stress is shaped by multiple psychosocial factors, particularly organizational dynamics, workload, and family demands. Strengthening workplace support systems and promoting work-life balance are critical to reducing stress in this sector.